2018
DOI: 10.1080/10428194.2018.1499904
|View full text |Cite
|
Sign up to set email alerts
|

The risk of tuberculosis in cancer patients is greatest in lymphoma and myelodysplastic syndrome/myeloproliferative neoplasm: a large population-based cohort study

Abstract: Patients with cancer are at high risk for tuberculosis (TB). This study combined the Israeli databases of cancer and TB and examined the development of TB among all newly diagnosed cancer cases from 1993 to 2013. Patients were classified into groups according to their different malignancies. Among 495,335 cancer patients, 335 developed TB following cancer diagnosis. The cumulative incidence of TB following cancer diagnosis was highest among MDS/MPN (148.8/100,000 patients) and lymphoma (154.1/100,000 patients)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Among all cancers, patients with Kaposi sarcoma are at the highest risk of dying from tuberculosis and other infections (including HIV). The risk for tuberculosis in patients with cancer is due to the weak hostcaused by immunosuppression from the cancer itself or the chemotherapy [31][32][33], as well as local structural changes in the lungs by cancer or metastasis [34,35]. A retrospective study conducted between 2000 and 2015 estimated that tuberculosis-related mortality was 0.83% in the cancer population [33] compared to 0.28% in the general population [36].…”
Section: Discussionmentioning
confidence: 99%
“…Among all cancers, patients with Kaposi sarcoma are at the highest risk of dying from tuberculosis and other infections (including HIV). The risk for tuberculosis in patients with cancer is due to the weak hostcaused by immunosuppression from the cancer itself or the chemotherapy [31][32][33], as well as local structural changes in the lungs by cancer or metastasis [34,35]. A retrospective study conducted between 2000 and 2015 estimated that tuberculosis-related mortality was 0.83% in the cancer population [33] compared to 0.28% in the general population [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with several studies in which lymphoma increased the risk of the development of active TB. (Cheng et al, 2017;Ganzel et al, 2019) The incidence of TB in Non-Hodgkin lymphoma (NHL) patients is 35 times higher than in the general population. Furthermore, interleukin 10 (IL-10), which is increased in patients with NHL, has been implicated in the reactivation of TB.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators cautioned that patients with a background of MDS/MPN have a higher risk of developing TB. 4 The major host defense against TB is cell-mediated immunity. It has been reported that there are serious defects in the lymphoid system in addition to abnormalities in the myeloid populations of MDS patients, such as decreased absolute numbers of T lymphocytes and markedly decreased CD4+/CD8+ ratio.…”
Section: Discussionmentioning
confidence: 99%
“…investigated 195 MDS patients and revealed 12 TB patients in this cohort, 50% of whom had extrapulmonary involvement. 4 Thus, the initial symptom of TB appears to be extrapulmonary, which may be common in an immuno - compromised host.…”
Section: Discussionmentioning
confidence: 99%